The displacement of families of population Anbar governorate: The destinationand and problems - Sauod, Hassan Khalf; Misahaan, Mothana; Ahmed, lamyaa (Al-Adab Journal, 2020)
The research aims at clarifying the phenomenon of displacement as a problem that has negative consequences through identifying the number of families of Al-Anbar Governorate displaced inside Iraq and the most important directions of displacement inside Al-Anbar Governorate and outside it, and the most important problems that they suffer from. The importance of the research comes in clarifying the geographical nature of the phenomenon of displacement as a population crisis that Iraq encounter it in general and Al-Anbar governorate in particular. The analytical descriptive approach has been relied on in studying the phenomenon of displacement through the number and ratios of displaced families to the population of Al-Anbar governorate as a whole during the period (2014-2017) and showing its geographical distribution in the governorates of Iraq. The results of the field study have been relied on through using a questionnaire form in clarifying the problems that the displaced families suffer from.The current research has arrived at a number of results, the most important of them are:The total number of the displaced families of Al-Anbar governorate reached to (273356) families in the period (2014-2017), however, the number in 2014 reached to (200994), (73.5%) which is the highest percentage in compared with the percentages of the following years, while the lowest percentage was in 2017, where the number of displaced is (2054), (0.8%) of the total families of Al-Anbar governorate.The highest number of the displaced families was for the families which were displaced inside Al-Anbar governorate, i.e. from the areas of the military conflict to safer areas and did not cross the borders of the province with a large percentage that reached to (52.4%) of the total families displaced in the period (2014-2017).The displaced families of Al-Anbar governorate faced many problems, including security problems, where the victims of murder accounted for (12.7%) of the size of the surveyed sample, while the percentage of arrested people was (29.5%), and the missing people, whose fate was not known, was the highest percentage (57.8%).The displaced families of Al-Anbar governorate suffered from social problems that were represented by poor social adaptation in the hosting areas (48%) of the sample size. The economic problems represented by material suffering are the most suffering economic problems by families in Al-Anbar governorate during displacement, at a high rate of (54%).The high percentage of the unemployed in the displaced families after the displacement compared to the percentage before the displacement, increased from (27%) to (85%), with a decrease in the level of monthly income of (74%) of the families surveyed after displacement to which reach to (less than 250) thousands Iraqi dinars, and it does not meet their needs. As for the families whose monthly income was (750 - and more) thousand Iraqi dinars, it was (1%) only.